The morality of assisted reproduction and genetic manipulation - Maurizio Mori
The author analyzes the pros and cons of various forms of assisted reproduction, including the use of so-called 'genetic manipulation'. He shows how in ethics the only arguments with any chance of reaching a consensus (or at least an agreement) are those of the rational type, based on universally acceptable ethical principles or corroborated by empirical facts and real life experience (as the starting point for identifying problems requiring analysis). After an analysis in which he identifies the incoherence and inconsistency of arguments against assisted reproduction, the author defends the right of human beings to decide autonomously about the most healthy forms of procreation, including those involving genetic manipulation. His starting point is the moral principle by which it is morally preferable to intervene in natural processes (as opposed to not intervening) whenever this implies preventing and reducing disease and suffering